BASIC CONCEPTS AND THE NATURE OF THE COMPANY’S INVESTMENT - V. S. Balabanov; E. V. Dmitrieva (Модернизация, инновация, развитие, 2016)
Investment activity is an important component in the successful development of the company in many ways it achieves its objectives, in particular, to increase the company’s revenue, and therefore, the budget of the country and the population. Therefore, the creation of optimalconditions for investment activities is a major factor of economic growth. In this paper, the notion of investment, are different definitions of the term, a classification of investments by various characteristics, the characteristic of investment companies.